Recent Advances in Screening Methods for the Functional Investigation of Lytic Polysaccharide Monooxygenases - Wang, Damao; Li, Yanping; Zheng, Yuting; Hsieh, Yves S. Y. (Frontiers in Chemistry, 2021)
Lytic polysaccharide monooxygenase (LPMO) is a newly discovered and widely studied enzyme in recent years. These enzymes play a key role in the depolymerization of sugar-based biopolymers (including cellulose, hemicellulose, chitin and starch), and have a positive significance for biomass conversion. LPMO is a copper-dependent enzyme that can oxidize and cleave glycosidic bonds in cellulose and other polysaccharides. Their mechanism of action depends on the correct coordination of copper ions in the active site. There are still difficulties in the analysis of LPMO activity, which often requires multiple methods to be used in concert. In this review, we discussed various LPMO activity analysis methods reported so far, including mature mass spectrometry, chromatography, labeling, and indirect measurements, and summarized the advantages, disadvantages and applicability of different methods.